2022
DOI: 10.1097/md.0000000000030175
|View full text |Cite
|
Sign up to set email alerts
|

Immunological characteristics of IgG4-related Kuttner tumors

Abstract: Immunoglobulin G4-related disease (IgG4-RD) has recently been well recognized and Kuttner tumor is known to be a chronic sclerosing sialadenitis, representing the focal manifestation of IgG4-RD, in the submandibular gland (SMG). This study is to evaluate the immunologic features of IgG4-related Kuttner tumor in the SMG. We retrospectively chose 13 patients who were confirmed as having Kuttner tumor by surgical biopsy between May 2012 and January 2019. The fine-needle aspiration cytology, serum antibody levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…EBV initially infects the oropharyngeal epithelium and then persists in memory B cells [ 44 , 45 ]. Even though lymphocyte infiltration is a common feature for non-specific types of sialadenitis [ 46 ], Lin et al [ 47 ] found an increased number of memory B cells in the inflammatory infiltrates of submandibular gland samples from patients with IgG4-RD compared to patients with primary Sjögren’s syndrome and healthy controls. Due to its persistence in memory B cells, the presence of EBV DNA in the IgG4-positive samples could hence be in part explained by the dense lymphocyte infiltration and the possible overrepresentation of B lymphocytes in the tissue samples from patients with IgG4-positive sialadenitis, as presented by Lin et al [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV initially infects the oropharyngeal epithelium and then persists in memory B cells [ 44 , 45 ]. Even though lymphocyte infiltration is a common feature for non-specific types of sialadenitis [ 46 ], Lin et al [ 47 ] found an increased number of memory B cells in the inflammatory infiltrates of submandibular gland samples from patients with IgG4-RD compared to patients with primary Sjögren’s syndrome and healthy controls. Due to its persistence in memory B cells, the presence of EBV DNA in the IgG4-positive samples could hence be in part explained by the dense lymphocyte infiltration and the possible overrepresentation of B lymphocytes in the tissue samples from patients with IgG4-positive sialadenitis, as presented by Lin et al [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the presence of viral DNA is not a sign of activity and would require more in-depth investigations, such as mRNA studies, to assess the virus activity. Third, since the DNA in the FFPE samples is more fragmented than in fresh tissue samples and salivary gland tissues with CS might comprise relatively low cellularity due to extensive fibrosis in the tissue [ 46 ], the DNA copies might have been undetectable even with the highly sensitive PCR. Furthermore, some regional variation in the virus distribution within the tissue might occur and the punch biopsies represent only a small portion of the salivary gland.…”
Section: Discussionmentioning
confidence: 99%